2009
DOI: 10.1200/jco.2009.27.15_suppl.9504
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory analysis of comprehensive geriatric assessment results and overall survival in 233 consecutive elderly cancer patients

Abstract: 9504 Background: Performance status (PS) is the main clinical parameter used by most oncologists to assess the ability of elderly cancer patients to tolerate chemotherapy and estimate prognosis. The results of comprehensive geriatric assessment (CGA) for elderly cancer patients were analyzed to investigate the impact of each CGA functional, physical, cognitive, and affective domain on overall survival in relation to performance status. Methods: CGA was used for 233 consecutive elderly cancer patients aged 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The predictive value of geriatric assessments for all-cause mortality was reported in 25 studies (Table 3). Six studies addressed the association of a summary score with mortality: all six found that frail patients showed poorer overall survival (100%) [21, 23-24, 28 -29, 57,63]. In these studies, median survival was between 1.6 and 3.7 times longer for fit patients compared to frail subjects.…”
Section: All-cause Mortalitymentioning
confidence: 99%
“…The predictive value of geriatric assessments for all-cause mortality was reported in 25 studies (Table 3). Six studies addressed the association of a summary score with mortality: all six found that frail patients showed poorer overall survival (100%) [21, 23-24, 28 -29, 57,63]. In these studies, median survival was between 1.6 and 3.7 times longer for fit patients compared to frail subjects.…”
Section: All-cause Mortalitymentioning
confidence: 99%